Nitrate and nitrite in the diet: How to assess their benefit and risk for human health. Issue 1 (14th October 2014) - Habermeyer, Michael; Roth, Angelika; Guth, Sabine; Diel, Patrick; Engel, Karl‐Heinz; Epe, Bernd; Fürst, Peter; Heinz, Volker; Humpf, Hans‐Ulrich; Joost, Hans‐Georg; Knorr, Dietrich; de Kok, Theo; et al.
<x xml:space="preserve">Abstract</x> Nitrate is a natural constituent of the human diet and an approved food additive. It can be partially converted to nitrogen monoxide, which induces vasodilation and thereby decreases blood pressure. This effect is associated with a reduced risk regarding cardiovascular disease, myocardial infarction, and stroke. Moreover, dietary nitrate has been associated with beneficial effects in patients with gastric ulcer, renal failure, or metabolic syndrome. Recent studies indicate that such beneficial health effects due to dietary nitrate may be achievable at intake levels resulting from the daily consumption of nitrate‐rich vegetables. N‐nitroso compounds are endogenously formed in humans. However, their relevance for human health has not been adequately explored up to now. Nitrate and nitrite are per se not carcinogenic, but under conditions that result in endogenous nitrosation, it cannot be excluded that ingested nitrate and nitrite may lead to an increased cancer risk and may probably be carcinogenic to humans. In this review, the known beneficial and detrimental health effects related to dietary nitrate/nitrite intake are described and the identified gaps in knowledge as well as the research needs required to perform a reliable benefit/risk assessment in terms of long‐term human health consequences due to dietary nitrate/nitrite intake are presented.